Pengaruh Bauran Pemasaran Terhadap Keputusan Berkuliah di Politeknik Balekambang Jepara - P, Purwati; Khasib, Zakiya Ramadlanti Nor; Ustiyasari, Ririn Indah; Alamia, Rosita (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research investigates the influence of the marketing mix (product, price, promotion, place) on the decision to study at the Balekambang Jepara Polytechnic, using quantitative methods on 30 student respondents, through multiple linear regression analysis, validity, reliability, normality, multicollinearity, heteroscedasticity, test t, f test, and coefficient of determination, which shows that price has a significant influence on the decision to study, while product, promotion and place variables do not have a significant effect partially, but simultaneously, these four variables influence the decision to study with a contribution of 67.8 %.